Petroleum exploration in Nepal - Bashyal, R. P. (Journal of Nepal Geological Society, 1998)
The southern part of Nepal comprising of Terai plain and Churia foothills are the prospecting area for petroleum exploration. Geological, geochemical and seismic surveys are carried out during the last decade. Such investigations have indicated a fairly good source rocks in the Melpani and Swat formations of the Surkhet Group and also in the Gondwana and Lakharpata groups. Similarly, the reservoir and seal rocks are also adequately identified. The seismic survey confirms various kinds of traps. The oil generation, expulsion and migration are considered to have been contemporaneous with or to have postdated the formation of the traps. His Majesty's Government of Nepal has designed a Production Sharing Contract with attractive work and fiscal terms including the "Seismic Option" and "No Ring Fencing" incentives. The promotional activities have resulted to conclude the petroleum agreements for exploration in Block 10 (Biratnagar) by Shell International (1986-1990) and Block 3 (Nepalgunj) and Block 5 (Chitwan) by Texana Resources Co., USA.